The reasoning agent: agency in the capability approach and some implications for development research and practice - Garcés, Pablo (Iberoamerican Journal of Development Studies, 2023)
Amartya Sen’s capability approach (CA) is a freedom-centered and agency-oriented framework to the assessment of individual and social states. Indeed, it regards agency as having intrinsic, instrumental, and constructive importance. Thus, there is a growing literature exploring how to empirically capture agency. However, relatively less has been said about what the CA agency entails on its own terms. That discussion hinges on two themes: rationality, and freedom. Contrary to the dominant approach, rational choice theory, which proposes a selfish, calculative, atomistic chooser, the CA proposes a multi-motivated, multidimensional, plural, and reflective chooser. That is, instead of a rational, the CA suggests a reasoning agent, accounting for such an agent has important implications for the conduct of inquiry, including the philosophy of science. They might be better tackled in the latter is given its due.
Keywords: capability; agency; rationality; freedom; reasoning